Health care seeking among pulmonary tuberculosis suspects and patients in rural Ethiopia: a community-based study - Yimaldu Tilahun; Holm-Hansen Carol; Yimer Solomon; Bjune Gunnar (BMC, 2009)
Abstract Background Health care seeking is a dynamic process that is influenced by socio-demographic, cultural and other factors. In Ethiopia, there are limited studies regarding the health seeking behaviour of tuberculosis (TB) suspects and TB patients. However, a thorough understanding of patients' motivation and actions is crucial to understanding TB and the treatment of disease. Such insights would conceivably help to reduce delay in diagnosis, improve treatment adherence and thereby reduce transmission of TB in the community. The objective of this study was to describe and analyze health care seeking among TB suspects and pulmonary TB (PTB) cases in a rural district of the Amhara Region in Ethiopia. Methods Study kebeles were randomly selected in a cross-sectional study design. House-to-house visits were conducted in which individuals aged 15 years and above in all households of the kebeles were included. Subjects with symptoms suggestive of TB were interviewed about their health seeking behaviour, socio-demographic and clinical factors using a semi-structured questionnaire. Logistics regression analysis was employed to assess associations between the independent and outcome variables. Results The majority, 787 (78%), TB suspects and 33 (82.5%) PTB cases had taken health care actions for symptoms from sources outside their homes. The median delay before the first action was 30 days. In logistics regression, women (AOR 0.8, 95% CI 0.6, 0.9) were found to be less likely to visit a medical health provider than men. Those with a long duration of cough (AOR 1.5, 95% CI 1.03, 2.1) and those with a previous history of TB (AOR 1.5, 95% CI 1.03, 2.3) were more likely to visit a medical health provider compared to those with a shorter duration of cough and with no history of TB. Conclusion The majority of TB suspects and PTB cases had already taken health care actions for their symptoms at the time of the survey. The availability of a simple and rapid diagnostic TB test for use at the lowest level of health care and the involvement of all health providers in case finding activities are imperative for early TB case detection.